Mobilisasi Sumber Daya Pada Aksi Kamisan Padang - Laura Azzhahra; Eka Vidya Putra (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
Abstract The number of human rights violations that occurred and not finding solutions to human rights problems led to the emergence of many social movements in society. One such movement is the Kamisan Action. The Kamisan action was a silent demonstration carried out against the demands of past serious human rights violations which was first carried out in Jakarta. This action has been widely spread in various areas, one of which is in the city of Padang, West Sumatra. In the city of Padang, this action has been going on for a long time, but interestingly, this movement has persisted so far even though the participants in it are not in direct contact with human rights issues in Jakarta. The purpose of this study was to find out what resources were owned by the Kamisan Padang action from how the mobilization was carried out to maintain the movement. The theory used is the mobilization of resources from Anthony Oberschall. This study uses a case study qualitative research approach. The informant selection technique is a purposive sampling technique. Data collection is done by means of observation, interviews and documentation studies. The results of the research that have been obtained in the field are, first, the actors, the symbols of the Kamisan Action, external support and tactics used to mobilize the movement. Keywords: Social Movement, Kamisan Action, Human Rights and Human Rights Violations